2008
DOI: 10.1038/ki.2008.102
|View full text |Cite
|
Sign up to set email alerts
|

Effects of different ACE inhibitor combinations on albuminuria: results of the GUARD study

Abstract: Clinical practice guidelines recommend blockers of the renin-angiotensin system alone or in combination with other agents to reduce blood pressure and albuminuria in patients with type 2 diabetes. Dihydropyridine calcium channel blockers, however, may lower blood pressure but not albuminuria in these patients. Here we tested the hypothesis that combining an ACE inhibitor with either a thiazide diuretic or a calcium channel blocker will cause similar reductions in blood pressure and albuminuria in hypertensive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
85
1
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 152 publications
(91 citation statements)
references
References 21 publications
3
85
1
2
Order By: Relevance
“…First, the dose of trichlormethiazide was increased to achieve further blood pressure reduction, although the use of highdose diuretics is not recommended in terms of preventing coronary heart disease. 41,42 Second, olmesartan was used in a single dose; however, the increase in the dose of ARB may be a choice of treatment to intensify the antihypertensive effect.…”
Section: Combined Antihypertensive Therapy With Olmesartan T Ishimitsmentioning
confidence: 99%
“…First, the dose of trichlormethiazide was increased to achieve further blood pressure reduction, although the use of highdose diuretics is not recommended in terms of preventing coronary heart disease. 41,42 Second, olmesartan was used in a single dose; however, the increase in the dose of ARB may be a choice of treatment to intensify the antihypertensive effect.…”
Section: Combined Antihypertensive Therapy With Olmesartan T Ishimitsmentioning
confidence: 99%
“…Recently, the GUARD study in the United States 10 showed treatment with an ACEI (benazepril) plus a diuretic (hydrochlorothiazide) in patients with diabetic nephropathy reduced albuminuria to a greater extent than an ACEI plus CCB (amlodipine). These results called into question whether a diuretic or CCB is more suitable as a second-line agent with a renin-angiotensin system inhibitor.…”
Section: Discussionmentioning
confidence: 99%
“…The Gauging Albuminuria Reduction With Lotrel in Diabetic Patients With Hypertension trial has also demonstrated that the concomitant use of ACEIs and diuretics reduces microalbuminuria. 7 However, secondary analysis of the Avoiding Cardiovascular Events Through Combination Therapy in Patients Living With Systolic Hypertension (ACCOMPLISH) trial revealed the progression of chronic kidney disease in patients treated with a combination of ACEIs/diuretics. 8 In our study, the reduction in the urine albumin-to-creatinine ratio values was significantly larger in the losartan/HCTZ group than in the maximal-ARB group.…”
Section: Discussionmentioning
confidence: 99%
“…2 However, the rate of diuretic prescription in Japan is still low because of the associated adverse metabolic effects, including hypokalemia, hyperuricemia, and the harmful influences on glucose and lipid metabolism. 6 Furthermore, it is still controversial whether a combination of rennin-angiotensin system (RAS) inhibitors and diuretics confers beneficial effects with regard to renal 7,8 and cardiovascular outcomes. 9 However, complete blockade of the RAS through increased doses of ARBs is recommended, based on the clinical benefits observed in patients with cardiovascular disease.…”
Section: Introductionmentioning
confidence: 99%